2012
DOI: 10.2478/s11535-012-0065-9
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence and population genetic structure of the whooper swan Cygnus cygnus and mute swan Cygnus olor in Lithuania and Latvia

Abstract: Coexistence and population genetic structure of the whooper swan Cygnus cygnus and mute swan Cygnus olor in Lithuania and Latvia IntroductionCoexistence between closely related species in a given habitat or region has been of interest to researchers for decades [1][2][3][4]. Species with diverse population structures are generally better adapted to changing environmental conditions and can more successfully utilize new types of habitats [5]. As a result of global environmental change, closely related species t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
1
9
1
Order By: Relevance
“…The three primers used allowed to separate the majority of individuals studied. Our findings disagree with results of a study by Butkauskas et al (2012) based on partial mitochondrial D-loop sequences, as they found only one haplotype in mute swans breeding and wintering in Latvia and Lithuania suggesting monotypic genetic structure. This discrepancy might be explained by the different methods used: in the study of Butkauskas et al (2012) diversity acquired via maternal inheritances was analysed, whereas our data involves nuclear variability of individuals.…”
contrasting
confidence: 99%
“…The three primers used allowed to separate the majority of individuals studied. Our findings disagree with results of a study by Butkauskas et al (2012) based on partial mitochondrial D-loop sequences, as they found only one haplotype in mute swans breeding and wintering in Latvia and Lithuania suggesting monotypic genetic structure. This discrepancy might be explained by the different methods used: in the study of Butkauskas et al (2012) diversity acquired via maternal inheritances was analysed, whereas our data involves nuclear variability of individuals.…”
contrasting
confidence: 99%
“…There have been particularly large increases after around 1985 (Axbrink 1999, Green & Lindström 2014, Nilsson 2014) which may be due to changes in agricultural practices that have favoured the Whooper Swan (Nilsson 2014). Similar increases have been observed in Finland (Valkama et al 2011), Estonia (Luigujoe et al 2002, Boiko et al 2014 and Latvia and Lithuania (Butkauskas et al 2012, Boiko et al 2014.…”
Section: Introductionsupporting
confidence: 67%
“…An important question is whether interactions between the two swan species may cause either a limitation of the population expansion of Whooper Swans in Oslo and Akershus, or a replacement of Mute Swans by Whooper Swans. In both Sweden (Svensson et al 1999) and Latvia and Lithuania (Butkauskas et al 2012) Whooper Swans have replaced Mute Swans in some areas. Although Whooper Swans rarely breed in saltwater where Mute Swans are common, and Whooper Swans do not have competition from Mute Swans at small lakes in forested areas, there is habitat overlap in particular at rich freshwater lakes (Gjershaug et al 1994, Svensson et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…DNA was extracted from bone samples using the Qiagen DNeasy Tissue Kit following the manufacturer's instructions with an overnight incubation at 558C. A 335 bp portion of the mitochondrial Control Region (CR) was amplified using the primer pair Cygn-1F (5 0 GGTTATGCATATTCGTGCATAGAT 3 0 )/ Cygn-3R (5 0 ACGTATGGGCCTGAAGCTAGT 3 0 ) [35]. Each PCR reaction (10 ml) consisted of: 0.4 mg ml 21 BSA, 0.75 mM MgCl 2 (Bioline), 1 Â PCR buffer (Bioline), 2.5 mM dNTPs (Bioline), 0.5 mM of each primer, 0.05 U Taq Polymerase (Bioline), and 1 ml DNA.…”
Section: Materials and Methods (A) Source Of Specimensmentioning
confidence: 99%